2015
DOI: 10.5539/gjhs.v8n3p49
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life for Saudi Patients With Heart Failure: A Cross-Sectional Correlational Study

Abstract: Introduction:Heart failure is a major public health issue and a growing concern in developing countries, including Saudi Arabia. Most related research was conducted in Western cultures and may have limited applicability for individuals in Saudi Arabia. Thus, this study assesses the quality of life of Saudi patients with heart failure.Materials and Methods:A cross-sectional correlational design was used on a convenient sample of 103 patients with heart failure. Data were collected using the Short Form-36 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
53
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 43 publications
12
53
1
7
Order By: Relevance
“…In this study, we found that patients with CHF had lower quality of life in all domains of the WHOQOL-BREF especially in environmental health domain (mean score of 38.56) and an overall quality life, which indicate that they know that their heath is poor and affecting their HRQOL. This nding is congruent with other previous study (25). This consistence result might be heart failure is a serious condition and leads to poor quality of life when the condition is not managed with heart failure management's.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found that patients with CHF had lower quality of life in all domains of the WHOQOL-BREF especially in environmental health domain (mean score of 38.56) and an overall quality life, which indicate that they know that their heath is poor and affecting their HRQOL. This nding is congruent with other previous study (25). This consistence result might be heart failure is a serious condition and leads to poor quality of life when the condition is not managed with heart failure management's.…”
Section: Discussionsupporting
confidence: 92%
“…However, this study did not corroborate those findings, possible due to the underlying Jordanian cultural domain. Jordanians tend to hide their emotional feelings during illness from their families and the public, and they try to avoid asking for social and emotional support (27 (27). It should be noted that while the social and emotional domains obtained better scores than the physical, these were still lower scores of the global studies (12).…”
Section: Discussionmentioning
confidence: 93%
“…It is well-known that there are many factors affecting the QOL for patients with HF. These factors include but are not limited to: age, gender, culture, social support, and marital status (AbuRuz, Alaloul, Saifan, Masa'deh, & Abusalem, 2015;Alaloul, AbuRuz, Moser, Hall, & Al-Sadi, 2016), functional class, duration of HF, left ventricular ejection fraction (LVEF), other comorbidities and psychosocial status (Chung, Moser, Lennie, & Frazier, 2012). It has been shown that social support improved patients' health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…One of the traditional religious customs among Muslim and Arabic cultures is to provide social support to persons when they are sick or in need for assistance (AbuRuz et al, 2015). The trajectory for HF patients is characterized by deterioration of physical functioning resulting in acute medical crises that often lead to hospitalization, dependency, and impairment in QOL (Huang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%